Full bore imaging of combustion and quantitative AFR PLIF with a multi-component fuel and co-evaporating tracers - Williams, B; Wang, X; Ewart, P; Stone, R; Ma, H; Walmsley, H; Cracknell, R; Stevens, R; Wallace, S; Richardson, D (2008)
A technique has been developed for full bore imaging, and a high speed video camera used to obtain images that have been processed for soot temperature and loading, and flame growth. The soot measurements have been made with a colour ratio technique that avoids the need for an in-situ absolute radiation calibration. Instead, the spectral response of the camera has to be determined for each of the red, green and blue channels. Planar Laser-Induced Fluorescence (PLIF) has been extensively used for visualizing species of combustion and reacting flows. However, the relationship between PLIF signal strength and species concentration is complicated by other dependencies, so careful calibration is essential. In order to study the effects of evaporation of a multi-component fuel in an IC engine, a gasoline-like component fuel has been devised which has three components of low, medium and high-volatility. Each component is made from two non-fluorescing constituents chosen so that the component (as a whole) will co-evaporate with one of three selected tracers: namely acetone, toluene or 1,2,4-trimethylbenzene (TMB). Calibration results are presented along with fuel concentration distributions derived from the PLIF images that have been analyzed on a cycle-by-cycle basis. © IMechE 2007.